Mast Cell Infiltration in Human Brain Metastases Modulates the Microenvironment and Contributes to the Metastatic Potential - Roy, Ananya; Libard, Sylwia; Weishaupt, Holger; Gustavsson, Ida; Uhrbom, Lene; Hesselager, Göran; Swartling, Fredrik J.; Pontén, Fredrik; Alafuzoff, Irina; Tchougounova, Elena (Frontiers in Oncology, 2017)
Metastatic brain tumors continue to be a clinical problem despite new therapeutic advances in cancer treatment. Brain metastases (BM) are among the most common mass lesions in the brain that are resistant to chemotherapies, have a very poor prognosis and currently lack any efficient diagnostic tests. Predictions estimate that about 40% of lung and breast cancer patients will develop BM. Despite this, very little is known about the immunological and genetic aberrations that drive tumorigenesis in BM. In this study, we demonstrate the infiltration of mast cells (MCs) in a large cohort of human BM samples with different tissues of origin for primary cancer. We applied patient-derived BM cell models to the study of BM cell-MC interactions. BM cells when co-cultured with MCs demonstrate enhanced growth and self-renewal capacity. Gene set enrichment analyses indicate increased expression of signal transduction and transmembrane proteins related genes in the co-cultured BM cells. MCs exert their effect by release of mediators such as IL-8, IL-10, matrix metalloprotease 2 (MMP2) and vascular endothelial growth factor (VEGF), thereby permitting metastasis. In conclusion, we provide evidence for a role of MCs in brain metastasis. Our findings indicate MCs capability of modulating gene expression in BM cells and suggest that MCs can serve as a new target for drug development against metastases in the brain.